Design and Development of Information Security Framework for Cloud Computing - Krishan Dutt, Pardeep Singh Cheema (International Journal of Advanced Science and Technology, 2020)
Cloud computing could be a service model during which the computing resources like software package, hardware and information area unit delivered as a service through an online browser or light-weight desktop machine over the net. Cloud computing has inflated its acceptance in recent years. Despite of getting variety of advantages, users area unit still disturbed concerning security in cloud thanks to losing the management of their own data once outsourced in cloud surroundings. the protection is a crucial feature altogether kinds of info systems, the cloud computing isn't any exception. The confidentiality, integrity and accessibility area unit the key problems poignant security of knowledge in cloud beside trait of users and cloud service suppliers. There area unit increasing security and privacy issues from the purpose of read of each the enterprises and also the people of their outsourced information in cloud. many security management standards and measures are meant to safeguard the cloud however withal cloud security is at a high risk thanks to the innovative hacking techniques. The Information Security Management (ISM) in an exceedingly cloud is that the method that focuses on counteracting structure risk, disasters and crises. Cloud computing faces major issues thanks to its study characteristics despite the technological innovations that have created it a possible answer. The l quality and utility of the cloud surroundings has created it the soft target of cloud crimes.in the paper Design and development of information security framework for cloud computing model is proposed for secure access and authorization.